Development of SARS-CoV-2 vaccines: challenges, risks, and the way forward - Vipin M. Vashishtha; Puneet Kumar (Taylor & Francis Group, 2021)
The COVID-19 pandemic mandates the development of a safe and effective Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) vaccine. This review analyzes the complexities, challenges, and other vital issues associated with the development of the SARS-CoV-2 vaccine. A brief review of the immune responses (innate, antibody, and T-cell) to SARS-CoV-2, including immune targets, correlates of protection, and duration of immunity is presented. Approaches to vaccine development including different vaccine platforms, critical attributes of novel vaccine candidates, the status of the ongoing clinical trials, and the ways to speed up vaccine development are also reviewed. Despite a historical average success rate of only 6%, and a usual gestation period of 10-12 years for the development of a new vaccine, the world is on the verge of developing COVID-19 vaccines in an extraordinary short time span.